Silence, screen, and spectacle : rethinking social memory in the age of information and new media - Freeman, Lindsey A.; Nienass, Benjamin; Daniell, Rachel (Remapping cultural history, 2014)
In an age of information and new media the relationships between remembering and forgetting have changed. This volume addresses the tension between loud and often spectacular histories and those forgotten pasts we strain to hear. Employing social and cultural analysis, the essays within examine mnemonic technologies both new and old, and cover subjects as diverse as U.S. internment camps for Japanese Americans in WWII, the Canadian Indian Residential School system, Israeli memorial videos, and the desaparecidos in Argentina. Through these cases, the contributors argue for a re-inte.